2014
DOI: 10.3133/ofr20141144
|View full text |Cite
|
Sign up to set email alerts
|

Behavior and dam passage of juvenile Chinook salmon and juvenile steelhead at Detroit Reservoir and Dam, Oregon, March 2012-February 2013

Abstract: For more information on the USGS-the Federal source for science about the Earth, its natural and living resources, natural hazards, and the environment-visit http://www.usgs.gov or call 1-888-ASK-USGS For an overview of USGS information products, including maps, imagery, and publications, visit http://www.usgs.gov/pubprodTo order this and other USGS information products, visit http://store.usgs.gov Suggested citation: Beeman, J.W., Hansel, H. C., Hansen, A.C., Evans, S.D., Haner, P.V., Hatton, T.W., Kofoot, E.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Rainbow Trout occupied the surface habitat (0-9 m), Chinook Salmon were generally 14-23 m deep, and Kokanee were the deepest (Monzyk et al 2013). Also, Chinook Salmon were observed in small schools (usually < 100 fish) while rearing in reservoirs and are known to congregate in the forebay of reservoirs (Beeman et al 2013). Kabata and Cousens (1973) reported that newly hatched copepodids are nearly motionless for approximately 30 min before actively swimming, and Poulin et al (1990) reported that inactive copepodids sink at a rate of 0.12 cm/s.…”
Section: Discussionmentioning
confidence: 99%
“…Rainbow Trout occupied the surface habitat (0-9 m), Chinook Salmon were generally 14-23 m deep, and Kokanee were the deepest (Monzyk et al 2013). Also, Chinook Salmon were observed in small schools (usually < 100 fish) while rearing in reservoirs and are known to congregate in the forebay of reservoirs (Beeman et al 2013). Kabata and Cousens (1973) reported that newly hatched copepodids are nearly motionless for approximately 30 min before actively swimming, and Poulin et al (1990) reported that inactive copepodids sink at a rate of 0.12 cm/s.…”
Section: Discussionmentioning
confidence: 99%
“…The detection probabilities of the arrays were empirically estimated to be at or near 1.0 during each year of study. Further details of the telemetry detection equipment can be found in Beeman et al [20][21][22].…”
Section: Methodsmentioning
confidence: 98%
“…This 8 km long reservoir in the west slope of the Cascade mountain range was created in 1963 by the construction of Cougar Dam on the South Fork of the McKenzie River about 74 km east of Eugene, Oregon. During 2011 and 2012, we macroscopically examined 281 juvenile Chinook salmon of natural origin when selecting candidates for surgical implantation of transmitters for a study of in-reservoir behavior and dam passage; details of the source study are described by Beeman et al [20][21][22]. The fish we report on were captured from within Cougar Reservoir using a 91.7 m-long Lampara seine that fished up to 7.6 m deep.…”
Section: Methodsmentioning
confidence: 99%